Evaluación de los posgrados de la Facultad de Odontología de la Universidad de Antioquia entre 1982 y 1995 (componentes curricular y administrativo)* - Ossa-de D., Nury; Gualdrón-M., Carmen Sofía (Revista Facultad de Odontología Universidad de Antioquia, 2017)
The curricular and administrative components were considered in one articule because the two form an unity. In the curricula was analized the general objectives, study plans, courses, contents, methods, evaluation and programs. It was done by using differents instruments such as inquires and interviews among the different people involved such as: alumni, students, professors, coordinators, and the existing documentation. In relation to the administrative aspect, was evaluated the organizations, the planing control, location, administratives tactics, orientation politics of the graduate studies directive organism, the normative and everything related to material resources, infrastructure, bibliografics resources and didactic aids.